2021
DOI: 10.1016/j.bioactmat.2020.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and characterization of anti-thrombotic and anti-oxidative Gastrodin-modified polyurethane for vascular tissue engineering

Abstract: Vascular grafts must avoid negative inflammatory responses and thrombogenesis to prohibit fibrotic deposition immediately upon implantation and promote the regeneration of small diameter blood vessels (<6 mm inner diameter). Here, polyurethane (PU) elastomers incorporating anti-coagulative and anti-inflammatory Gastrodin were fabricated. The films had inter-connected pores with porosities equal to or greater than 86% and pore sizes ranging from 250 to 400 μm. Incorporation of Gastrodin into PU films resulted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 98 publications
1
19
0
Order By: Relevance
“…The peaks at 1723 cm −1 and 1529 cm −1 were ascribed to C = O and –NH stretching of the urethane group (OCONH) of PU, respectively. The characteristic peak at 3372 cm −1 for gastrodin was significantly reduced in PU, indicating its role in cross-link polymerization, as demonstrated in our previous report [ 51 ]. The broad peaks at 1092 cm −1 and 1034 cm −1 corresponded to the vibration of a phosphate group (PO 4 ), suggesting that n-HA was composited into the scaffolds.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The peaks at 1723 cm −1 and 1529 cm −1 were ascribed to C = O and –NH stretching of the urethane group (OCONH) of PU, respectively. The characteristic peak at 3372 cm −1 for gastrodin was significantly reduced in PU, indicating its role in cross-link polymerization, as demonstrated in our previous report [ 51 ]. The broad peaks at 1092 cm −1 and 1034 cm −1 corresponded to the vibration of a phosphate group (PO 4 ), suggesting that n-HA was composited into the scaffolds.…”
Section: Resultssupporting
confidence: 79%
“…Huang et al also showed that gastrodin can protect hBMSCs and RAW 264.7 cells from oxidative stress, ameliorate trabecular micro-architecture, and inhibit osteoclastogenesis in ovariectomized rats (OVX) [ 44 ]. However, as gastrodin is easily metabolized in vivo , we considered that gastrodin combined with PU could achieve sequential release of gastrodin, thereby reducing the inflammatory response (i.e., TNF-α and IL-1β levels) in RAW 264.7 cells [ 51 ]. Thus, we designed a gastrodin-delivery composite scaffold and explored its immunomodulatory effects on vascular bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Gastrodin, which is applied in cardiovascular diseases, can lower blood viscosity and regulate inflammation reactions. Zheng et al [ 25 ] fabricated Gastrodin-loaded PU scaffolds, and found that the Gastrodin modified grafts showed greater potential in preventing thrombogenesis and inflammations.…”
Section: Preventing Vascular Incidents For Long-term Lumen Patencymentioning
confidence: 99%
“…For long-term patency, thrombogenesis is the key factor leading to vascular occlusion. Vascular grafts, as the foreigner directly exposed to blood flux in vasculature, are easy to cause protein deposition and provoke thrombogenesis [ 24 , 25 ]. The aggregation of insoluble fibrin, platelet, and red cells induces the coagulation cascades and results in thrombus formation [ [26] , [27] , [28] ].…”
Section: Introductionmentioning
confidence: 99%